Simulation Testing of Maritime Cyber-Physical Systems: Application of Model-View-ViewModel. (21st January 2022) - Lee, Dong-Chul; Seo, Kyung-Min; Park, Hee-Mun; Kim, Byeong Soo
Abstract : From the perspective of the system of systems development, system-level functional testing is required for designing subsystems. This study utilizes modeling and simulation techniques to analyze the operational behaviors of the subsystems and confirm data communication between them. The targeted system in the study is a naval combat system (NCS), which is a typical type of defense cyber-physical system (CPS). Three types of models were designed for the simulation testing of the NCS: a combat-management model for simulating the overall computational activities, physical models to confirm the intrasubsystem behaviors, and data integration models to test the intersubsystem communications. These models are realized with the Model-View-ViewModel design pattern, which strongly facilitates graphical user interfaces being decoupled from model logic and data. We consider underwater combat scenarios as an application. Six significant physical subsystems within the NCS are simulated and tested: a ship-steering system, an inertial navigation system, a global navigation satellite system, a periscope, sonar systems, and a plotting board. We expect that the proposed work will play a principal role when analyzing the behaviors and communications of defense CPSs and providing an environment for functional testing as a digital twin.